Wildflowers : Seek Adventure! Go Outside! Have Fun! Find What Blooms Beyond Your Backyard! - Romero, Libby; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2018)
"Information about wildflowers for children"--
Wildflower Report: Basal Angiosperms -- Monocots -- Water-Plantains/Alismataceae -- Arums/Araceae -- Lilies/Liliaceae -- Colchicums/Colchicaceae -- Meadow Saffrons/Colchicaceae -- Trilliums/Melanthiaceae -- Death Camases/Melanthiaceae -- False Hellebores/Melanthiaceae -- Wildflower Report: Flower Life Cycle -- Orchids/Orchidaceae -- Irises/Iridaceae -- Daffodils/Amaryllidaceae -- Asparagus/Asparagaceae -- Pickerelweeds/Pontedariaceae -- Spiderworts/Commelinaceae -- Cattails/Typhaceae -- Bur-reeds/Typhaceae -- Wildflower Report: Time to Bloom -- Eudicots -- Poppies/Papaveraceae -- Fumitories/Fumariaceae -- Barberries/Berberidaceae -- Buttercups/Ranunculaceae -- Saxifrages/Saxifragaceae -- Wood Sorrels/Oxalidaceae -- Wildflower Report: Attracting Pollinators -- St. John's Worts/Hypericaceae -- Violets/Violaceae -- Flaxes/Linaceae -- Geraniums/Geraniaceae -- Evening Primroses/Onagraceae -- Loosestrifes/Lythraceae -- Wildflower Report: Invasive Species -- Mallows/Malvaceae -- Rock-Roses/Cistaceae -- Capers/Capparaceae -- Mustards/Brassicaceae -- Wildflower Report: Petal Patterns -- Roses/Rosaceae -- Peas/Fabaceae -- Pinks/Caryophyllaceae -- Buckwheats/Polygonaceae -- Sundews/Droseraceae -- Purslanes/Portulacaceae -- Fig-Marigolds/Aizoaceae -- Four O'clocks/Nyctaginaceae -- Cacti/Cactaceae -- Wildflower Report: Looking at Leaves -- Touch-me-nots/Balsaminaceae -- Phlox/Polemoniaceae -- Primroses/Primulaceae -- Pitcher-plants/Sarraceniaceae -- Heaths/Ericaceae -- Wintergreens/Pyrolaceae -- Wildflower Report: Weird Flowers -- Gentians/Gentianaceae -- Dogbanes/Apocynaceae -- Milkweeds/Asclepiadaceae -- Madders/Rubiaceae -- Borages/Boraginaceae -- Waterleaves/Hydrophyllaceae -- Morning-glories/Convolvulaceae -- Nightshades/Solanaceae -- Wildflower Report: Dangerous Flowers -- Acanthuses/Acanthaceae -- Bladderworts/Lentibulariaceae -- Verbenas/Verbenaceae -- Mints/Lamiaceae -- Figworts/Scrophulariaceae -- Valerians/Valerianaceae -- Bellflowers/Campanulaceae -- Asters/Asterateae -- Carrots/Apiaceae -- Wildflower Report: Building Better Habitats -- State Flowers.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 8-12.
Grades 4 to 6.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Wild flowers -- North America -- Identification -- Juvenile literature; Wild flowers -- Identification; JUVENILE NONFICTION -- Reference; JUVENILE NONFICTION -- Science & Nature -- Botany; JUVENILE NONFICTION -- Science & Nature -- Flowers & Plants; Wild flowers -- Identification; North America; Electronic books- OSLIS; Literature; Juvenile works; Literature; Electronic books